Potential impact of investments in drought tolerant maize in Africa - La Rovere, Roberto; Kostandini, Genti; Abdoulaye, Tahirou; Dixon, John; Mwangi, Wilfred; Guo, Zhe; Banziger, Marianne (International Maize and Wheat Improvement Center, 2010)
This study was conducted in collaboration with HarvestChoice (IFPRI) and evaluates the potential impacts of the Drought Tolerant Maize for Africa (DTMA) project run by CIMMYT and the International Institute for Tropical Agriculture (IITA) in 13 countries of eastern, southern and West Africa, describing cumulative economic and poverty-reduction benefits to farmers and consumers in those countries over 2007-16, from higher yields and from diminished season-to-season yield fluctuations, through the adoption by farmers of improved, drought tolerant maize varieties. At the most likely rates of adoption drought tolerant maize can generate US$ 0.53 billion from increased maize grain harvests and reduced risk over the study period, assuming conservative yield improvements. Assuming more optimistic yield gains, the economic benefit is nearly US$ 0.88 billion in project countries. If all current improved varieties were replaced with drought tolerant ones, this could help more than 4 million people to escape poverty and many millions more to improve their livelihoods. If as expected farmers who adopt drought tolerant maize continue to grow it beyond 2016, the returns on investments to this work will become even more significant.